Microplastics in river sediments in two streams in an Andean region of Peru - Franklin Canchari; José Iannacone (Revista Brasileira de Recursos Hídricos)
ABSTRACT The objective of this study was to determine the concentration, types and characteristics (size, morphology and color, as well as polymer composition) of MPs in surface sediments in two streams in an Andean region of Peru. Surface sediment samples were collected in Ishoj stream (11 sampling sites) and Uyru Rume stream (8 sampling sites), and density separation was performed using high-density saline solution (zinc chloride, ZnCl2) to separate the MPs from the sediment. The concentration of MPs ranged from 0 - 2216 items/Kg (Ishoj stream) and 0 - 6383 items/Kg (Uyru Rume stream). In both streams, the maximum concentration of MPs was in the sites located near the dumps (solid waste collection, downstream) and the minimum value was found in the sites located in the upper zone. The size, morphology and predominant color in both streams were less than 1 mm, fragment and transparent, respectively. No MPs were found in pellet form. PP (polypropylene) was the predominant MPs in Raman analysis. All MPs were secondary. This study report contamination by MPs in streams in Andean zones.